(untitled) (Forum Penelitian Agro Ekonomi, 2016)
The main problem of rural development in Indonesia is related with coordination among the main actors and the focus of activities. In this paper, the main problem of rural development in Indonesia based on the experience of China in the previous program and rural development is examined. In some part of the paper, analysis was focused on the Rural Agribussines Development Program (PUAP), an initiative program of Ministry of Agricultural for poverty alleviation and rural development. Similar with the previous program in rural development that initiated by the government, PUAP is a top down project approach; most of the initiative come from the central goverment. The mechanism of project decision is dominated by the goverment role and structure, and less of rural community initiative. The maximum impact of the PUAP project is an entry point for agricultural development in rural areas.